2018
DOI: 10.1186/s13195-018-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor remains unchanged in cerebrospinal fluid of patients with Alzheimer’s disease and vascular dementia

Abstract: BackgroundIncreasing evidence suggests that cerebral vascular dysfunction is associated with the early stages of Alzheimer’s disease (AD). Vascular endothelial growth factor (VEGF) is one of the key players involved in the development and maintenance of the vasculature. Here, we hypothesized that VEGF levels in cerebrospinal fluid (CSF) may be altered in AD patients with vascular involvement, characterized by the presence of microbleeds (MB), and in vascular dementia (VaD) patients compared to controls.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In contrast, Chakraborty et al [30] found no significant difference in CSF VEGF levels across patients with VaD, AD, and controls. Ke et al [28] also did not find significant differences in intrathecal levels of VEGF or BNDF in patients with ischemic cerebrovascular diseases and VCI compared with controls.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Chakraborty et al [30] found no significant difference in CSF VEGF levels across patients with VaD, AD, and controls. Ke et al [28] also did not find significant differences in intrathecal levels of VEGF or BNDF in patients with ischemic cerebrovascular diseases and VCI compared with controls.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, these inconsistent results suggest that angiogenic factors may play a yet incompletely understood role in multiple forms of dementia, including vascular and neurodegenerative pathologies. Studies with VEGF CSF levels in AD populations have also yielded inconsistent results [29, 30, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of VEFG also reflects the pathological progress of AD. A negative correlation between the level of VEGF and the development progress of AD’s pathological process has been observed [ 35 ]. VEGF can act directly on many types of nerve cells to play a neurotrophic and neuroprotective role, enhance cell activity and survival, and promote axon regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the role of VEGF-A signaling in patients with AD. Most studies find increased levels of VEGF-A in the serum or CSF of patients with AD ( 18, 4345 ), with a minority showing reduced ( 22, 46 ) or unchanged levels ( 47 ). Increased VEGF-A levels are also seen in brain homogenates from the TgCNDR8 ( 48 ) and APP/PS1 mouse models of AD ( 49 ), as well as in endothelial cells of arteries, veins, and capillaries from aged WT mice( 50 ), mouse models of APP over expression ( 24, 51 ), mutant Tau mice ( 52 ), and patients with AD ( 5355 ).…”
Section: Discussionmentioning
confidence: 99%